(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present paper was designed to examine the intergenerational differences in adjustment. A sample of 180 (60 grandparents 60 parents and 60 their young adults) between the age range of 18-76 was selected from rural and urban areas. The participants were administered the measures of bell adjustment inventory. Obtained data were analyzed by applying descriptive statistic, one way anova. It was found that grandparents were found more adjusted on all domains of adjustment, while young adults were found not adjusted on any domain of adjustment as compared to grandparents while parents were found not adjusted on health and home adjustment as compared to grandparents.